2006
DOI: 10.1002/jez.b.21093
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic memory of developing mammalian dentition

Abstract: Structures suppressed during evolution can be retraced due to atavisms and vestiges. Atavism is an exceptional emergence of an ancestral form in a living individual. In contrast, ancestral vestige regularly occurs in all members of an actual species. We surveyed data about the vestigial and atavistic teeth in mammals, updated them by recent findings in mouse and human embryos, and discussed their ontogenetic and evolutionary implications. In the mouse incisor and diastema regions, dental placodes are transient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
109
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 96 publications
(112 citation statements)
references
References 53 publications
2
109
1
Order By: Relevance
“…It has been proposed that atavistic structures can only arise when a rudiment has been retained (27). In addition, the supernumerary teeth in Eda-overexpressing mice are thought to arise by rescue of a rudimentary tooth germ (28). We therefore examined whether the ability of Eda to restore lost upper pharyngeal teeth is dependent on the presence of rudiments in the upper pharynx.…”
Section: Eda Overexpression Restores Teeth To the Upper Pharynx Of Thementioning
confidence: 99%
“…It has been proposed that atavistic structures can only arise when a rudiment has been retained (27). In addition, the supernumerary teeth in Eda-overexpressing mice are thought to arise by rescue of a rudimentary tooth germ (28). We therefore examined whether the ability of Eda to restore lost upper pharyngeal teeth is dependent on the presence of rudiments in the upper pharynx.…”
Section: Eda Overexpression Restores Teeth To the Upper Pharynx Of Thementioning
confidence: 99%
“…At least in primates, the timing of tooth development could be modified at many checkpoints leading to full emergence, which is requisite by the time of weaning. Currently, sequence and timing of tooth primordium initiation, crown mineralization, and emergence are useful tools with which to reconstruct not only life history and phylogeny but also homology of tooth identities and embryonic tissues (Peterkova et al, 2006). Furthermore, variability in the timing of tooth germ formation may bear upon the likelihood that these teeth will develop at all in a given taxon (Luckett, 1993).…”
Section: Red In Tooth and Jawmentioning
confidence: 99%
“…By studying genetic regulation of cusp morphogenesis in extant model organisms, we can understand the mechanisms that may underlie morphological changes during evolution. Previous studies have found that mutant mice can have severe abnormalities in tooth morphology (3)(4)(5)(6), and some authors have explored the evolutionary implications of tooth number modifications in mutants (7)(8)(9). However, to our knowledge, mutations in extant mouse or human samples that mimic morphologies of close ancestors have not been reported.…”
mentioning
confidence: 99%